UJI DAYA HAMBAT FILTRAT ZAT METABOLIT Actinomycetes DARI KEBUN RAYA BOGOR TERHADAP PERTUMBUHAN Malassezia furfur SECARA IN VITRO - Venita Octavia Tambunan, (2020)
Malassezia furfur is one of the fungi which causes pityriasis versicolor or tinea versicolor. The widespread of fungal infections and the lack of therapeutic options can develop fungal resistance and become a serious problem in the future. Actinomycetes are Gram-positive bacteria that can produce secondary metabolites such as antifungal, antibacterial, and anticancer. This study aims to determine the effectiveness of Actinomycetes metabolite filtrate as an antifungal agent against in vitro growth of M. furfur. The research type is a laboratory experimental study with post test only group design using Actinomycetes metabolites concentration of 25%, 50%, 75%, 100%, ketoconazole as positive control, and aquades as negative control. Antifungal testing was performed using well difussion method on Sabouraud Dextrose Agar Media. From the four concentrations, the average diameter of clear zone were 6.025mm, 8.05mm, 9.1mm, 9.9mm respectively, followed by ketoconazole 35.3mm. There are significant differences between each treatment group, p < 0.05. Actinomycetes metabolite filtrate has antifungal effectiveness to inhibit the growth of M. furfur by binding with ergosterol in cell wall that will disrupt the integrity of fungal cell wall.